Thermophilic mycoflora and physical parameters of the compost for the white button mushroom, Agaricus bisporus - Mediratta, V; Vijay, B; Singh, S K; Ahlawat, O P; Singh, Ajay (Mushroom Research, 2015)
Please see the full text